Association between blood cobalt ion concentrations and anemia and cardiovascular diseases: novel evidence of toxicity resulting from metal implants - Xu, Shenghao; Chen, Bo; Wang, Hao; Tang, Xiongfeng; Xiao, Jianlin; Qin, Yanguo (Frontiers in Nutrition, 2025)
BackgroundCobalt ions released from metal objects pose potential systemic toxicity risks, yet comprehensive epidemiological evidence linking blood cobalt ion concentrations with anemia and cardiovascular disease (CVD) remains limited. This study aims to investigate these associations and explore exposure thresholds.MethodsWe utilized data from the National Health and Nutrition Examination Survey from 2015 to 2018. Outcomes included anemia, angina pectoris, arrhythmia, heart attack, heart failure, myocardial infarction, and stroke. We first used multivariate linear regression to demonstrate that metal implants are associated with elevated blood cobalt ion concentrations. Afterward, multivariable logistic regression, restricted cubic splines, and threshold effect analyses were applied to evaluate dose–response relationships between cobalt ion concentrations and disease.ResultsParticipants with metal implants exhibited 0.42 nmol/L higher blood cobalt concentrations than those without (95% confidence interval [CI]: 0.33–0.51). Each 1 nmol/L increase in cobalt was associated with a 36% higher anemia risk (adjusted odds ratio [OR]: 1.36, 95% CI: 1.31–1.41). Non-linear relationships were observed for CVD (inflection point: 3.94 nmol/L), with cobalt ion concentrations below this threshold showing stronger associations (OR: 1.27, 95% CI: 1.12–1.45). Cobalt exposure increased the risks of angina pectoris, arrhythmia, heart attack, heart failure, and stroke (all p < 0.05), but not myocardial infarction. Stratified analyses revealed heightened susceptibility in males.ConclusionMetal object-derived cobalt exposure demonstrates significant dose-dependent associations with anemia and multiple CVD subtypes. These findings underscore the systemic toxicity of cobalt ions and advocate for enhanced clinical surveillance of blood cobalt levels in patients with metal implants.